Forensic anthropology : 2000 to 2010 - Black, Sue M.; Ferguson, Eilidh (CRC Press, 2011)
"Advances in our ability to analyse information from skeletal remains and subsequent developments in the field of forensic anthropology make it possible to identify more victims of homicides, mass-fatality disasters, and genocide. Summarizing the vast collection of international literature that has developed over the past decade, Forensic Anthropology: 2000 to 2010 explores critical themes fundamental to this evolving topic. A superior supplemental text for any physical anthropology or archaeology class, this volume provides an ideal starting point for advanced exploration and more detailed analysis of select areas. Each chapter presents an overview of the theme under discussion, identifies present trends in research, and suggests areas in which future research could be developed. Topics discussed include: Age determination in juveniles and adults; Sex, race, and ancestry determination; Stature determination; Dental and facial identification; Skeletal trauma and bone pathology; Taphonomy and comparative osteology; Identification from soft tissues. Heavily referenced, each chapter contains extensive bibliographies that facilitate further study. The scope of the book's coverage and the careful presentation of meticulous research make it an essential resource for those seeking deeper exploration of this growing field"--Provided by publisher.